Harmonic structure, a promising microstructure design. Issue 7 (3rd July 2022) - Ameyama, Kei; Cazes, Fabien; Couque, Hervé; Dirras, Guy; Kikuchi, Shoichi; Li, Jia; Mompiou, Frédéric; Mondal, K.; Orlov, Dmytro; Sharma, Bhupendra; Tingaud, David; Vajpai, Sanjay K.
Abstract : The harmonic structure is a recently introduced concept paving the way for engineering metallic materials to achieve excellent mechanical performance. They consist of soft coarse-grained regions (Core) that are three-dimensionally surrounded by a connected network of hard ultra-fine grained regions (Shell). The interaction in these Core–Shell regions produces a synergistic effect, during plastic deformation, leading to superior mechanical properties that are extremely important in practical applications. The current review paper is aimed at providing a critical assessment on this novel concept of microstructure design. It also involves the identification and critical discussion of key issues which deserve additional studies. GRAPHICAL ABSTRACT: UF0001